Evaluation of Morphology of Premature Ventricular Contraction on 12-Lead Electrocardiogram (Bangladesh Heart Journal, 2017)
Background-Evaluation of different morphology of premature ventricular contraction (PVC) in 12-lead ECG might reflect the presence or absence of myocardial diseases and determine PVC foci. It is important for ablation procedure and it can help in pre-procedural planning and potentially may improve ablation outcome.Methods and Results-In this study, 12-lead Electrocardiogram (ECG) of 50 patients with or without structural cardiac diseases, who had experienced PVC, were obtained. PVC QRS duration, contour, pattern, unifocal or multifocaland different morphology in various lead were evaluated. PVC-QRS morphology of 50 ECGs showed QRSd d 140ms was 60%, >140ms was 24%, >160ms was 16%. QRS notching 40ms was 16%, smooth contour was 42%. The morphology of PVCs in lead V1, RBBB morphology was 36%, LBBB morphology was 64%; in lead V1 & V2, high r 8%, low r 4%. QRS wave polarity in lead I negative (QS, Qr, or rS wave pattern) 28%, positive (R-wave pattern) 52%; in lead II, III, avF, positive 76%. Of these RR or Rr pattern 20%, R pattern 56%. Negative 24%. QRS transition in chest lead, 16% transition occur at V4 V5, 48% at V3-V4, 4% at V2-V3, 36% at V1-V2 level. The pattern of PVCs were bigeminy 24%, trigeminy 6%, couplet 4%, salvos 12%, R on T 2%, VT 6%. Of the 32 PVCs originating from the RVOT, 8 were classified as of free-wall origin, 24 of septal, 14 of left, 26 of right, 4 of proximal, and 2 of distal origin. Of the 6 PVCs originating from the LVOT, 4 were originated from the LVOT close to the left coronary cusp and 2 were originated from the LVOT close to the right coronary cusp. Of the 12 PVCs originated from LV fascicle, 12 of posterior fascicle origin and none from anterior fascicle origin.Conclusion-12-lead ECG is a simple, inexpensive and noninvasive tool to detect PVCs and facilitate their localization. By evaluating morphology of PVC, we can also predict the structural and functional state of heart.Bangladesh Heart Journal 2016; 31(2) : 75-79